2007
DOI: 10.4161/cc.6.23.5095
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Heterogeneity of Mesenchymal Stem Cell Populations: Clues to their Therapeutic Efficacy

Abstract: Mesenchymal stem cells (MSCs) have demonstrated therapeutic efficacy in a variety of disease models and human clinical trials. The widespread benefits of MSCs have recently been attributed to their capacity to secrete soluble factors that promote tissue repair by stimulating angiogenesis and suppressing inflammation, apoptosis, and immune cell function. However, these functional attributes are inconsistent with the designation of MSCs as stem cells, which by definition lie at the apex of a hierarchy of lineage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
143
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(152 citation statements)
references
References 64 publications
5
143
1
3
Order By: Relevance
“…A loss of adipogenic differentiation capacity might be caused by tumor cells through attenuation of TP53 expression that promotes osteoblast differentiation [40], thus possibly inhibiting differentiation into adipocytes. MSCs from all three sources showed osteogenic and chondrogenic potential, which demonstrates the multipontentiality of MSCs derived from NCx and CeCa; however, as in BM, these results may suggest that cultures of MSCs could represent an admixture of morphologically, phenotypically, and functionally different cells, as some authors have proposed [41,42]. Interestingly, fibrocartilage was observed in assays from NCx and CeCa, whereas hyaline cartilage was predominant in pelleted micromass from BM, which suggests distinct functional capacities between MSCs from NCx and CeCa compared with BM.…”
contrasting
confidence: 40%
“…A loss of adipogenic differentiation capacity might be caused by tumor cells through attenuation of TP53 expression that promotes osteoblast differentiation [40], thus possibly inhibiting differentiation into adipocytes. MSCs from all three sources showed osteogenic and chondrogenic potential, which demonstrates the multipontentiality of MSCs derived from NCx and CeCa; however, as in BM, these results may suggest that cultures of MSCs could represent an admixture of morphologically, phenotypically, and functionally different cells, as some authors have proposed [41,42]. Interestingly, fibrocartilage was observed in assays from NCx and CeCa, whereas hyaline cartilage was predominant in pelleted micromass from BM, which suggests distinct functional capacities between MSCs from NCx and CeCa compared with BM.…”
contrasting
confidence: 40%
“…A major contributor to these inconsistent clinical outcomes may be the inherent variability in the immunosuppressive capacity of MSC lines due to differing tissues of origin, manufacturing processes, and donor-specific differences (10,(21)(22)(23). Although this functional heterogeneity is well known, no reliable predictors of MSC immunosuppressive capacity have been identified (3,24).…”
Section: Morphological Features Of Mscs After Ifn-γ Stimulation Corrementioning
confidence: 99%
“…MSCs populations exhibit considerable intra-and inter-population heterogeneity. It has been suggested that heterogeneous populations reflect the complexity of the stromal system in the bone marrow and the varied functions it performs to regulate tissue homeostasis and its contribution to the demonstrated functionality of MSCs in vivo [57,59]. As of present, it is still unclear which cell(s) types are the in vivo precursor cells that expand in culture in vitro as MSCs.…”
Section: Heterogeneity Of Bone Marrow Stem Cells and Mesenchymal Stemmentioning
confidence: 97%
“…Bone marrow derived MSCs display biochemical heterogeneity in phenotypes and functions -with potentially incredible biological and medical benefits and implications due to their known involvement in tissue repair, immunomodulation and inflammation [57][58][59][60][61]. MSCs populations exhibit considerable intra-and inter-population heterogeneity.…”
Section: Heterogeneity Of Bone Marrow Stem Cells and Mesenchymal Stemmentioning
confidence: 99%